The Nairobi pork value chain: Mapping and assessment of governance, challenges, and food safety issues - Murungi, Maurice K.; Muloi, Dishon M.; Muinde, Patrick; Githigia, S.M.; Akoko, James M.; Fèvre, Eric M.; Rushton, Jonathan; Alarcón, P. (Frontiers Media, 2021)
The Nairobi pork food system is a growing livestock sub-sector which serves as a source of food and livelihood to its inhabitants. The study aimed to map Nairobi's pork value chains, assess their governance, operational challenges and their impacts on food safety risks and management practices. Qualitative data were collected in seven focus group discussions and 10 key informants' interviews on animal movements and product flows, stakeholders' interactions, perceptions on system governance and challenges, and on their potential impact on food safety management. Quantitative data were obtained to show the importance of flows, business operations and market share. Thematic analysis was conducted to identify themes that provide understanding on the governance, challenges and food safety practices in each profile. The predominant chains identified were [1] The “large integrated company” profile which accounted for 83.6% of pork marketed through abattoirs, and was based on a well-structured supply system, with owned farms (representing 50% of their supply), contract farms and semi-contract farms and [2] Local independent abattoirs, accounting for 16.4%, are privately owned small-scale production, supplied mainly (70%) by small farmers from the immediate neighboring areas. The main challenges associated with governance themes included; (i) Inadequate/lack of enforcement of existing regulation (ii) Negative effect of devolution system of governance (iii) Pig traders' dominance (iii) Lack of association at all system nodes, and (iv) Male dominance across the pig system. The main challenges reported included; (i) Lack of capital to upscale (ii) Poor infrastructure (iii) Pig shortage (iv) Excessive regulation (v) Lack of training (vi) Diseases (v) Lack of knowledge (vi) Unfair competition. Food safety themes were associated with (i) Inadequate slaughter facilities forcing traders/farmers to undertake home slaughter (ii) Lack of knowledge on disease management (iii) Lack of training on hygienic practices in the slaughterhouse and (iv) Lack/insufficient capital to purchase equipment's to ensure proper hygiene e.g., boilers. The study provides insights into the structure of the pork system supplying Nairobi, the governance issues important to the stakeholders, challenges and food safety issues. The framework obtained can be used by policy makers and researchers to investigate and develop pork industry and for food safety and disease control programmes.